Changes of white matter integrity and structural network connectivity in nondemented cerebral small‐vessel disease. Issue 4 (26th August 2019) - Liu, Chengxia; Zou, Lin; Tang, Xiaoying; Zhu, Wenhao; Zhang, Guiling; Qin, Yuanyuan; Zhu, Wenzhen
Abstract : Background: Previous studies have found widespread impairment of white matter (WM) integrity and disruption of structural network connectivity in cerebral small‐vessel disease, but have not evaluated these changes jointly in nondemented patients. Purpose: To jointly investigate the microstructural impairment of WM and the related alterations of structural network topology in nondemented cerebral small‐vessel disease (CSVD‐ND). Study Type: Prospective. Population: Thirty‐seven CSVD‐ND patients and 34 elderly controls, who were age‐, sex‐, and education‐matched. Field Strength/Sequence: 3.0T/diffusion tensor imaging (DTI). Assessment: Clinical characteristics, lacunar infarct, and white matter hyperintensity (WMH) was assessed. A multiatlas likelihood fusion (MALF) algorithm was used for DTI‐based brain segmentation and network node defining. Then the alterations of WM integrity and structural network topology were investigated jointly. Statistical Tests: Student's t ‐test, chi‐square test, Mann–Whitney U ‐test, linear regression, Pearson correlation, and multiple comparison correction. Results: Decreased fractional anisotropy and increased trace values were observed in predefined structures ( P < 0.05, familywise error rate‐corrected), including major commissural fibers, projection fibers, and some association fibers. Topologically, both groups showed small‐worldness. CSVD‐ND patients showed reduced global and local efficiency ( P < 0.001). Despite widespread impairment of WM integrity, CSVD‐ND patients only showed reduced nodal efficiency in the right superior occipital gyrus and the right lingual gyrus ( P < 0.05, familywise error rate‐corrected). The nodal local efficiency of the right precuneus was associated with the processing speed after adjusting the effect of lacunar infarct and WMH ( r = –0.499, P = 0.038). Data Conclusion: WM integrity was widely impaired in nondemented CSVD patients but structural network connectivity was relatively preserved. DTI may potentially provide information for the pathophysiology of CSVD in the nondemented phase. Level of Evidence: 1 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2020;51:1162–1169.